Implementation of ‘Hablumminannas’ as Islamic value budget planning in non profit organization: phenomenological studies - Ani Setyowati; Tri Jatmiko Wahyu Prabowo (Journal of Islamic Accounting and Finance Research, 2022)
Purpose - The purpose of this study was to exsplore the implementation of Hablumminannas as a budget planning in Non-profit organization in Indonesian and to determine the preferences of the others non-profit organization to operate their business circle.Method - This study uses a phenomenological approach. In obtaining some information, the researcher used the interview method addressed to 15 informants who were at PT. Serkolinas Aman Nusantara spread throughout Indonesia.Result - The results of this study, top management and members of the organization know more about what are the top priorities in determining strategies to improve organizational performance and no one member of the organization feels disadvantaged in accordance with what is recommended by the Qoran, that the concept of Hablumminannas must always prioritize good relations with others.Implication - Especially in the non-profit organization sector so that they are in accordance with the guidelines of Islamic Values Hablumminannas.Originality - Provide detailed understanding of the implementation of budget planning through the Islamic values of Hablumminannas which are principled not to harm others through a phenomenological approach to non-profit organizations in Indonesia.